2018
DOI: 10.1002/rth2.12049
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double‐blind, placebo‐controlled, interventional phase IV investigation to assess the efficacy and safety of r‐hirudin gel (1120I.U) in patients with hematomas

Abstract: Essentials Efficacy and safety data on recombinant hirudin gels for the treatment of hematomas is limited.We assessed the clinical efficacy of a topical r‐hirudin gel in 199 patients with hematomas.Treated patients exhibited significant reductions in hematoma size and flare within 16 days.r‐hirudin gel treatment induces a complete resolution of hematomas and associated edema in 98%, and 99% of patients, respectively. BackgroundHirudin is the most potent direct thrombin inhibitor, and recombinant forms are rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…Orthopaedic surgical or traumatic injuries are often accompanied with impressive superficial symptoms that include vascular disorders (ecchymoses and subdermal hematomas), oedema and pain, as a common result of a physical trauma. Topical applications are frequently used to treat subdermal hematomas and consequent symptoms, and include anti-inflammatory and antioedematous treatments like heparin and/or other mucopolysaccharide gels and creams [8]. The present study confirmed that topical heparin is able to control these superficial symptoms.…”
Section: Resultssupporting
confidence: 83%
“…Orthopaedic surgical or traumatic injuries are often accompanied with impressive superficial symptoms that include vascular disorders (ecchymoses and subdermal hematomas), oedema and pain, as a common result of a physical trauma. Topical applications are frequently used to treat subdermal hematomas and consequent symptoms, and include anti-inflammatory and antioedematous treatments like heparin and/or other mucopolysaccharide gels and creams [8]. The present study confirmed that topical heparin is able to control these superficial symptoms.…”
Section: Resultssupporting
confidence: 83%